High-performance self-powered hydrogel flexible touch sensor and preparation method thereof
By introducing composite hydrogel and self-powered electrode structures into hydrogel flexible tactile sensors, the problem of insufficient sensitivity and self-powered performance in the prior art is solved, and the preparation of high-performance self-powered hydrogel flexible tactile sensors is realized, which expands its application range and increases the depth of mechanism research.
Patent Information
- Application Number
- CN202411954007.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
AI Technical Summary
The sensitivity and self-powered performance of existing hydrogel flexible tactile sensors need to be further improved, and it is difficult to meet the comprehensive performance requirements of practical application scenarios such as clinical medicine.
The composite hydrogel was prepared by mixing and dissolving the polymer monomer, crosslinking agent, initiator and electrolyte in a mixed solution of water and glycerol, and polymerizing under ultraviolet light to form a hydrogel. Combined with freeze-drying technology and electrolyte soaking, a composite hydrogel was prepared. Then, carbon paper carries α-MnO2 as the positive electrode, titanium electrode ears and zinc sheets as the negative electrodes, and a self-powered hydrogel flexible tactile sensor is constructed through a plastic film.
It realizes self-powered, high sensitivity, low detection limit, long service life, considerable output voltage and rechargeable performance, and gives the device the structural characteristics of bendable, stretchable and distorable, expanding its application range.
Smart Images

Figure CN119798516A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of flexible sensors, and in particular relates to a high-performance self-powered hydrogel flexible tactile sensor and a preparation method thereof. Background Art
[0002] Hydrogel materials have three-dimensional pore structures as well as performance characteristics such as biocompatibility and stretchability. Flexible electronic devices built based on hydrogel materials can communicate electronic devices and biological tissues, and have important research significance in fields such as biomedicine and information detection. Related research can produce application results that affect disciplines such as bioelectronics, the Internet of Things, and artificial intelligence.
[0003] High-performance self-powered hydrogel flexible tactile sensors can meet the requirements of comprehensive performance of equipment in practical application scenarios such as clinical medicine, and have considerable application prospects. However, the sensitivity and other key performance of existing hydrogel flexible tactile sensors still need to be further improved, and the self-powered performance of the device needs to be further developed. Summary of the invention
[0004] In view of this, the main object of the present invention is to provide a high-performance self-powered hydrogel flexible tactile sensor and a preparation method thereof.
[0005] To achieve the above object, the technical solution of the present invention is achieved as follows: An embodiment of the present invention provides a method for preparing a high-performance self-powered hydrogel flexible tactile sensor, the method comprising: Step 1: dissolving a polymer monomer, a cross-linking agent, an initiator, KOH, MnSO4, and ZnSO4 in a first mixed solution of water and glycerol to obtain a second mixed solution; Step 2: adding the second mixed solution of step 1 into a quartz mold, irradiating it under ultraviolet light, and obtaining a composite hydrogel through freeze drying technology and swelling process; Step 3: Use carbon paper to carry α-MnO2 as the positive electrode, use titanium tabs, use zinc sheets as the negative electrode, and encapsulate them through plastic film to obtain a self-powered hydrogel flexible tactile sensor.
[0006] In the above scheme, the molar ratio of the polymer monomer, crosslinking agent, photoinitiator, thermal initiator, KOH, MnSO4, ZnSO4, water and glycerol is 1000-16000:90-295:1-300:1-300:100-50000:0-50000:0-50000:100-60000:0-15000.
[0007] In the above scheme, the polymer monomer is at least one of acrylic acid, acrylamide, methyl methacrylate, ethyl acrylate, butyl acrylate, 2-phenylethyl acrylate, isooctyl acrylate and a mixture thereof.
[0008] In the above scheme, the group of the polymer monomer is a carboxylic acid group, a carboxylic acid salt, a sulfonic acid group, a sulfonic acid salt, a benzenesulfonic acid group, a benzenesulfonic acid salt, a phosphate group or a phosphate salt.
[0009] In the above scheme, the cross-linking agent is at least one of N,N'-methylenebisacrylamide and polyethylene glycol diacrylate.
[0010] In the above scheme, the initiator is at least one of ammonium persulfate, potassium persulfate, α-ketoglutaric acid, and photoinitiator 184.
[0011] In the above scheme, the step 2 specifically includes: the free radicals provided by the initiator under ultraviolet light irradiation cause the polymer monomer and the cross-linking agent to polymerize to form a hydrogel; the hydrogel is treated with freeze-drying technology to obtain a freeze-dried hydrogel, and then the freeze-dried hydrogel is immersed in a mixed solution of MnSO4 and ZnSO4 for more than 3 hours, taken out and washed with water to obtain a composite hydrogel loaded with electrolyte; wherein the molar amount of MnSO4 and ZnSO4 in every 10 ml of water is 50-50000:15-50000.
[0012] In the above scheme, the freeze-dried hydrogel is immersed in a mixed solution of MnSO4 and ZnSO4, and the molar amount of MnSO4 and ZnSO4 in every 10 ml of water is 50-50000:15-50000.
[0013] An embodiment of the present invention also provides a high-performance self-powered hydrogel flexible tactile sensor prepared by the preparation method described in any one of the above schemes.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The self-powered flexible tactile sensor constructed by the present invention endows the hydrogel flexible tactile sensor with the characteristics of self-power, high sensitivity and functional integration, expanding its application range and deepening its mechanism research. The high-performance self-powered hydrogel flexible tactile sensor prepared by the present invention not only has the properties of high sensitivity, low detection limit, long service life, considerable output voltage and rechargeability, but also has excellent structural characteristics such as bendability, stretchability and twistability. BRIEF DESCRIPTION OF THE DRAWINGS The drawings described herein are used to disclose a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 This is a self-powered hydrogel sample; Figure 2 It is a self-powered hydrogel soft-pack battery; Figure 3 is the sensitivity curve of a self-powered hydrogel tactile sensor; Figure 4 is the sensitivity curve of another self-powered hydrogel tactile sensor; Figure 5 is the output voltage of the self-powered hydrogel tactile sensor; Figure 6 Schematic diagram of the structure of the self-powered hydrogel tactile sensor. DETAILED DESCRIPTION
[0015] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0016] The same or similar numbers in the drawings of this embodiment correspond to the same or similar parts; in the description of the present invention, it should be understood that the directions or positional relationships indicated by the terms "upper", "lower", "left", "right", "inner", "outer", etc. are based on the directions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific direction, be constructed and operated in a specific direction. Therefore, the terms describing the positional relationship in the drawings are only used for illustrative purposes and cannot be understood as limitations on this patent. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.
[0017] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, article or device. In the absence of more restrictions, an element defined by the sentence "includes a ..." does not exclude the existence of other identical elements in the process, article or device including the element.
[0018] The embodiment of the present invention provides a method for preparing a high-performance self-powered hydrogel flexible tactile sensor, which is implemented by the following steps: Step 1: Step 1: Mix and dissolve a polymer monomer, a cross-linking agent, an initiator, KOH, MnSO4, and ZnSO4 in a first mixed solution of water and glycerol to obtain a second mixed solution; Specifically, the molar ratio of the polymer monomer, the crosslinking agent, the photoinitiator, the thermal initiator, KOH, MnSO4, ZnSO4, water and glycerol is 1000-16000:90-295:1-300:1-300:100-50000:0-50000:0-50000:100-60000:0-15000.
[0019] The polymer monomer, cross-linking agent and initiator are used to form a hydrogel, and KOH, MnSO4 and ZnSO4 constitute an electrolyte.
[0020] The polymer monomer is at least one of acrylic acid, acrylamide, methyl methacrylate, ethyl acrylate, butyl acrylate, 2-phenylethyl acrylate, isooctyl acrylate and a mixture thereof.
[0021] The group of the polymer monomer is a carboxylic acid group, a carboxylic acid salt, a sulfonic acid group, a sulfonic acid salt, a benzenesulfonic acid group, a benzenesulfonic acid salt, a phosphoric acid group or a phosphoric acid salt.
[0022] The cross-linking agent is at least one of N,N'-methylenebisacrylamide and polyethylene glycol diacrylate.
[0023] The initiator is at least one of ammonium persulfate, potassium persulfate, α-ketoglutaric acid, and photoinitiator 184.
[0024] Step 2: adding the second mixed solution of step 1 into a quartz mold, irradiating it under ultraviolet light, and obtaining a composite hydrogel through freeze drying technology and swelling process; Specifically, the free radicals provided by the initiator under ultraviolet light irradiation cause the polymer monomer and the cross-linking agent to polymerize to form a hydrogel; the hydrogel is treated with freeze-drying technology to obtain a dry and frozen hydrogel, and then the freeze-dried hydrogel is immersed in a mixed solution of MnSO4 and ZnSO4, wherein the molar amount of MnSO4 and ZnSO4 per 10 ml of water is 50-50000:15-50000, and the hydrogel is immersed for more than 3 hours, taken out and washed with water to obtain a composite hydrogel loaded with electrolyte.
[0025] The freeze-dried hydrogel is immersed in a mixed solution of MnSO4 and ZnSO4, wherein the molar amount of MnSO4 and ZnSO4 in every 10 ml of water is 50-50000:15-50000.
[0026] Step 3: Use carbon paper to carry α-MnO2 as the positive electrode, use titanium tabs, use zinc sheets as the negative electrode, and encapsulate them through plastic film to obtain a self-powered hydrogel flexible tactile sensor.
[0027] Specifically, the plastic film is an aluminum foil bag, parylene, PDMS film, ITO film or PU film.
[0028] Example The present invention provides five specific embodiments of a method for preparing a high-performance self-powered hydrogel flexible tactile sensor, and each embodiment is described in detail below.
[0029] Example 1 Step 1: Select polymer monomer acrylic acid (molar ratio of 12000), cross-linking agent N,N'-methylenebisacrylamide (molar ratio of 150), photoinitiator 184 (molar ratio of 150), and KOH (molar ratio of 20000), MnSO4 (molar ratio of 40000), and ZnSO4 (molar ratio of 5000) as electrolytes.
[0030] The above materials were mixed and dissolved in a solution consisting of water (molar ratio of 50,000), ensuring that all ingredients were fully dissolved and mixed evenly.
[0031] Step 2: Add the well-mixed solution into the quartz mold.
[0032] Irradiate under ultraviolet light for 15 minutes to allow the free radicals provided by the initiator to initiate the polymerization of the high molecular monomer and the cross-linking agent to form a hydrogel.
[0033] Step 3: The above hydrogel is treated by freeze-drying technology to obtain a freeze-dried hydrogel.
[0034] The freeze-dried hydrogel was immersed in a mixed solution of MnSO4 and ZnSO4 (the molar amounts of MnSO4 and ZnSO4 were 40000 and 10000 per 10 ml of water, respectively) for 4 h.
[0035] The resulting composite hydrogel was taken out and washed with water to obtain a composite hydrogel loaded with electrolytes.
[0036] Step 4: Use carbon paper to carry α-MnO2 as the positive electrode and connect it with a titanium pole ear.
[0037] A zinc sheet was used as the negative electrode.
[0038] By packaging in an aluminum foil bag, a self-powered hydrogel flexible tactile sensor was obtained.
[0039] Example 2 Step 1: Select polymer monomer acrylamide (molar ratio of 8000), cross-linking agent polyethylene glycol diacrylate (molar ratio of 250), ammonium persulfate (molar ratio of 200) as initiator, and KOH (molar ratio of 15000), MnSO4 (molar ratio of 20000), and ZnSO4 (molar ratio of 25000) as electrolyte.
[0040] The above materials were mixed and dissolved in a mixed solution consisting of water (molar ratio of 45000) and glycerol (molar ratio of 5000), ensuring that all ingredients were fully dissolved and mixed evenly.
[0041] Subsequent steps: Follow steps 2 to 4 in Example 1 to obtain a self-powered hydrogel flexible tactile sensor.
[0042] Example 3 Step 1: Select polymer monomer methyl methacrylate (molar ratio of 16000), cross-linking agent N,N'-methylenebisacrylamide (molar ratio of 90), potassium persulfate (molar ratio of 100) as initiator, and KOH (molar ratio of 50000), MnSO4 (molar ratio of 5000), and ZnSO4 (molar ratio of 45000) as electrolyte.
[0043] The above materials were mixed and dissolved in a solution consisting of water (molar ratio of 60,000), ensuring that all ingredients were fully dissolved and mixed evenly.
[0044] Subsequent steps: follow steps 2 to 4 in Example 1, but use parylene film during packaging to obtain a self-powered hydrogel flexible tactile sensor.
[0045] Example 4 Step 1: Select a mixture of polymer monomers ethyl acrylate and butyl acrylate (molar ratios of 6000 and 4000, respectively), a crosslinker polyethylene glycol diacrylate (molar ratio of 295), α-ketoglutaric acid (molar ratio of 300) as an initiator, and KOH (molar ratio of 10000), MnSO4 (molar ratio of 50000), and ZnSO4 (molar ratio of 0) as electrolytes.
[0046] The above materials were mixed and dissolved in a mixed solution consisting of water (molar ratio of 55000) and glycerol (molar ratio of 15000), ensuring that all ingredients were fully dissolved and mixed evenly.
[0047] Subsequent steps: follow steps 2 to 4 in Example 1, but use a PDMS membrane during encapsulation to obtain a self-powered hydrogel flexible tactile sensor.
[0048] Example 5 Step 1: Select polymer monomer 2-phenylethyl acrylate (molar ratio of 10000), cross-linking agent N,N'-methylenebisacrylamide (molar ratio of 100), photoinitiator 184 (molar ratio of 1) as initiator, and KOH (molar ratio of 30000), MnSO4 (molar ratio of 10000), and ZnSO4 (molar ratio of 40000) as electrolyte.
[0049] The above materials were mixed and dissolved in a solution consisting of water (molar ratio of 58000), ensuring that all ingredients were fully dissolved and mixed evenly.
[0050] Subsequent steps: The hydrogel composite was prepared according to step 2 of Example 1, but during the swelling process, the freeze-dried hydrogel was immersed in a mixed solution of MnSO4 and ZnSO4 (the molar amounts of MnSO4 and ZnSO4 were 50 and 15000 per 10 ml of water, respectively) for 5 hours.
[0051] After taking out and washing with water, the step 4 in Example 1 was followed, but an ITO film was used during packaging to obtain a self-powered hydrogel flexible tactile sensor.
[0052] The self-powered flexible tactile sensor constructed by the present invention endows the hydrogel flexible tactile sensor with the characteristics of self-power, high sensitivity and functional integration, expanding its application range and deepening its mechanism research. The high-performance self-powered hydrogel flexible tactile sensor prepared by the present invention not only has the properties of high sensitivity, low detection limit, long service life, considerable output voltage and rechargeability (such as Figure 3 , Figure 4 and Figure 5 ), and the device has excellent structural properties such as bendable, stretchable and twistable.
[0053] Figure 1-5 The sensitivity and output voltage of the self-powered hydrogel sample, self-powered hydrogel soft-pack battery, and self-powered hydrogel tactile sensor were demonstrated respectively; The embodiment of the present invention also provides a high-performance self-powered hydrogel flexible tactile sensor, the structure of which is as follows: Figure 6 As shown, it is prepared by the preparation method of any of the above embodiments.
[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention.
Claims
1. A method for preparing a high-performance self-powered hydrogel flexible tactile sensor, characterized in that: The method includes: Step 1: dissolving a polymer monomer, a cross-linking agent, an initiator, KOH, MnSO4, and ZnSO4 in a first mixed solution of water and glycerol to obtain a second mixed solution; Step 2: adding the second mixed solution of step 1 into a quartz mold, irradiating it under ultraviolet light, and obtaining a composite hydrogel through freeze drying technology and swelling process; Step 3: Use carbon paper to carry α-MnO2 as the positive electrode, use titanium tabs, use zinc sheets as the negative electrode, and encapsulate them through plastic film to obtain a self-powered hydrogel flexible tactile sensor.
2. The method for preparing a high-performance self-powered hydrogel flexible tactile sensor according to claim 1, characterized in that: The molar ratio of the polymer monomer, the crosslinking agent, the photoinitiator, the thermal initiator, KOH, MnSO4, ZnSO4, water and glycerol is 1000-16000:90-295:1-300:1-300:100-50000:0-50000:0-50000:100-60000:0-15000.
3. The method for preparing a high-performance self-powered hydrogel flexible tactile sensor according to claim 1 or 2, characterized in that: The polymer monomer is at least one of acrylic acid, acrylamide, methyl methacrylate, ethyl acrylate, butyl acrylate, 2-phenylethyl acrylate, isooctyl acrylate and a mixture thereof.
4. The method for preparing a high-performance self-powered hydrogel flexible tactile sensor according to claim 3, characterized in that: The group of the polymer monomer is a carboxylic acid group, a carboxylic acid salt, a sulfonic acid group, a sulfonic acid salt, a benzenesulfonic acid group, a benzenesulfonic acid salt, a phosphoric acid group or a phosphoric acid salt.
5. The method for preparing a high-performance self-powered hydrogel flexible tactile sensor according to claim 4, characterized in that: The cross-linking agent is at least one of N,N'-methylenebisacrylamide and polyethylene glycol diacrylate.
6. The method for preparing a high-performance self-powered hydrogel flexible tactile sensor according to claim 5, characterized in that: The initiator is at least one of ammonium persulfate, potassium persulfate, α-ketoglutaric acid, and photoinitiator 184.
7. The method for preparing a high-performance self-powered hydrogel flexible tactile sensor according to claim 6, characterized in that: The step 2 specifically comprises: the free radicals provided by the initiator under ultraviolet light irradiation polymerize the polymer monomer and the crosslinking agent to form a hydrogel; the hydrogel is treated by freeze-drying technology to obtain a freeze-dried hydrogel, and then the freeze-dried hydrogel is immersed in a mixed solution of MnSO4 and ZnSO4 for more than 3 hours, taken out and washed with water to obtain a composite hydrogel loaded with electrolyte; wherein the molar amount of MnSO4 and ZnSO4 in every 10 ml of water is 50-50000:15-50000.
8. The method for preparing a high-performance self-powered hydrogel flexible tactile sensor according to claim 7, characterized in that: The freeze-dried hydrogel is immersed in a mixed solution of MnSO4 and ZnSO4, wherein the molar amount of MnSO4 and ZnSO4 in every 10 ml of water is 50-50000:15-50000.
9. A high-performance self-powered hydrogel flexible tactile sensor prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Sensor and preparation method thereof, and application method of sensor
CN112111071A
Hydrogel complex and preparation method thereof
CN112113690A
Preparation method of self-powered multifunctional hydrogel sensor
CN115046464A
Integrated self-powered pressure sensor based on aqueous zinc ion battery and preparation method thereof
CN118670577A